Quantifying zooplankton species: use of richness estimators - Castilho, Maria Carolina de A. [UNESP]; Wisniewski, Maria Jose dos S.; Wisniewski, Celio; Silva, Erika dos S. (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2016)
Richness estimators (Jackknife 1, Bootstrap, Chao 1 and ACE) were used to relate zooplankton species richness with amount of water collected per sample and number of samples throughout the year for the limnetic region of Sapucai River compartment of Furnas reservoir, state of Minas Gerais, Brazil. Seven 100 L samples were collected in sequence using a motor pump, and seven 70 L samples were collected in sequence using a plankton net (68 mu m mesh size) in vertical hauls, to totalize 450 L, in three stations of the reservoir. Twelve monthly samplings were carried out over a year. The assessment of richness was made by analyzing the asymptotic behavior of the estimator curves. The samplings reached the asymptote from 350 L of collection with trawls and 400 L using a suction motor pump and reached the plateau on the 8th collection, which included both dry and rainy seasons. Regardless of the type of sampling, the volume of 400 L and eight sessions throughout the year is enough to register 90% of the zooplankton richness in the environment.
Keywords: Biodiversity; Cladocera; Rotifera; sampling effort; aquatic environments